A novel dynamical 3D smile measurement method to evaluate the effects of face-lifting surgery: Based on the optical structured light strategy - Li, Jia; Zhou, Junhong; Zhang, Jue (Optik (Stuttgart), 2015)
Assessment of plastic surgery is important for the therapy evaluation while there is no widespread accepted objective method used. This study proposes a novel optical technique to acquire the dynamical data of face muscle with potential to objectively evaluate the effect of surgery. This approach is based on the optical structured light measurement with the colored encoded stripe pattern. Through the calculation of the image phase shift of those projected stripe on the face and the optical system calibration, we get the accurate height of the face surface. 10 young subjects are involved. One high-speed camera is used to record their smile procedure and then data of each captured frame are calculated. All the results, which are at subpixel level, are accurate to 0.1mm and all the error s is below 5%, which is considered as enough accuracy. Meanwhile, a significantly high correlation between optical measurement and traditional standard measuring approach is observed (r2=0.99, p=2.97×10−12). Based on the results, our dynamical optical smile measurement shows enough high accuracy of in acquiring the moving information of every point on smile face. No secondary pollution would happen in the measurement technique with no touching or contacting the surgery area, which thus might induce a safer and cleaner way for the clinical evaluation of the face-lifting surgery with high spatial and temporal resolution.